Assessment of Amphibola crenata as a bioindicator of estuarine trace element pollution using biochemical and physiological endpoints - Nuwan A.L. De Silva; Islay D. Marsden; Sally Gaw; Chris N. Glover (Marine Pollution Bulletin, 2024)

Diversity and distribution of benthic dinoflagellates in Tonga include the potentially harmful genera Gambierdiscus and Fukuyoa - Phoebe A. Argyle; Lesley L. Rhodes; Kirsty F. Smith; D.Tim Harwood; Tuikolongahau Halafihi; Islay D. Marsden (Harmful Algae, 2023)

Physiological and biochemical responses of the estuarine pulmonate mud snail, Amphibola crenata, sub-chronically exposed to waterborne cadmium - Nuwan A.L. De Silva; Islay D. Marsden; Sally Gaw; Chris N. Glover (Aquatic Toxicology, 2023)

Population responses of the pulmonate gastropod, Amphibola crenata , reflect estuarine trace metal contamination - Nuwan A. L. De Silva; Islay D. Marsden; Rhian Taylor; Sally Gaw; Chris N. Glover (New Zealand Journal of Marine and Freshwater Research, 2022)
This study assessed the potential of the mud snail Amphibola crenata as a bioindicator of estuarine health. Multiple sites with varying contaminant inputs were identified within a small, shallow estuary (Avon‐Heathcote/Ihutai in the South Island of New Zealand). Population structures of field‐collected A. crenata were related to measurements of sediment trace metal profiles. Whole‐body soft tissue metal concentrations were significantly positively correlated with sediment trace metals for all elements analysed (arsenic, cadmium, copper, nickel, lead and zinc). In terms of population biomarkers, medium‐sized mud snails (7.9–17.9 mm shell length) dominated the population size structure at the most contaminated sites. That sites which were more highly enriched in trace metals were distinguishable by application of a simple population structure assessment, suggests that A. crenata has potential value for evaluating estuarine health. However, further investigation of other biotic and abiotic factors that may influence population structure are required.

Indigenous and local peoples’ values of estuarine shellfisheries: moving towards holistic‐based catchment management - Ani Alana Kainamu‐Murchie; Islay D. Marsden; Rawiri T. M. Tau; Sally Gaw; John Pirker (New Zealand Journal of Marine and Freshwater Research, 2018)
Estuaries support a wide range of human activities and values, but are one of the most anthropogenically impacted ecosystems in the world. Ki uta ki tai is a holistic view of waterways that is embodied within Ngāi Tahu environmental management, which acknowledges the connectivity between environmental systems and people with the environment. While this philosophy is referred to within current policies, management does not effectively account for or reflect this philosophy. This research evaluated indigenous and local socio‐cultural values provided by estuarine shellfisheries across Waitaha/Canterbury and found Ngāi Tahu place‐based interaction was impacted by management and anthropogenic inputs. Participants’ estuarine stressors aligned with global stressors. Experienced harvesters/fishers adapted their practices to these stressors, while less experienced harvesters/fishers visited high food‐risk sites. Effective management requires identifying the risks to socio‐cultural values towards accountability of activities, to meet the ethic of ki uta ki tai.

Reproduction, growth and size of a burrowing intertidal clam exposed to varying environmental conditions in estuaries - Suzanne C. Adkins; Islay D. Marsden; John G. Pirker (Invertebrate Reproduction & Development, 2016)

Does population structure and growth of an intertidal pulmonate snail reflect environmental conditions within a small estuary? - Islay D. Marsden; Isobel Swinscoe (Hydrobiologia, 2014)

Current status of cockle bed restoration in New Zealand - Islay D. Marsden; Suzanne C. Adkins (Aquaculture International, 2010)

Spatial and Temporal Variations in Trace Metal Concentrations in the Cockle, Austrovenus Stutchburyi from Otago, New Zealand - Barrie M. Peake; Islay D. Marsden; Ashley M. Bryan (Environmental Monitoring and Assessment, 2006)

A Field Experiment to Assess the Transplant Success of Salt Marsh Plants into Tidal Wetlands - Dana Thomsen; Islay D. Marsden; Ashley D. Sparrow (Wetlands Ecology and Management, 2005)

Seasonal variation in the reproductive activity and biochemical composition of the Pacific oyster (Crassostrea gigas) from the Marlborough Sounds, New Zealand - Jeffrey S. Ren; Islay D. Marsden; Alex H. Ross; David R. Schiel (New Zealand Journal of Marine and Freshwater Research, 2003)
Reproductive cycles of the Pacific oyster Crassostrea gigas (Thunberg) from the Marlborough Sounds, New Zealand, were followed between June 1998 and January 2000. Histological examination of the gonad confirms an annual cycle with a winter inactive period followed by rapid gonad development and a single short spawning period. The population gonad index correlated with seawater temperature and changes in tissue dry weight, condition index, and biochemical components. In winter, few individuals with early gametogenic stages were present and rapid development of primary oocytes (diam. 11 μm) occurred during spring (September‐November). The developmental rate and the diameter of mature oocytes (37 μm) was similar for the 1998 and 1999 seasons. For a standard 110‐mm‐length oyster, maximal tissue body weight and condition index were recorded in December. Rapid weight loss in January was length dependent and was attributed to spawning. Temperature was the environmental variable which best correlated with the timing of gametogenesis. Food availability (phytoplankton biomass) may have been responsible for inter‐annual variations. The biochemical composition (% glycogen, lipid, protein) of separated gonad and somatic tissues were variable seasonally and annually. Gametogenesis (oocyte diameter) was associated with increased gonad protein and glycogen and a decrease in lipid concentrations. These changes are similar to those in Pacific oyster populations from other parts of the world.

Shore‐level induced variations in condition and feeding of the mussel Perna canaliculus from the east coast of the South Island, New Zealand - Islay D. Marsden; Mark A. Weatherhead (New Zealand Journal of Marine and Freshwater Research, 1999)
Mussels (Perna canaliculus) (Gmelin, 1791) collected from mid and low tide rocky platforms along the east coast of the South Island of New Zealand differed in dry weight condition index between shore levels. Mussel condition was c. 15% lower at mid tide level than the low tide level and there was greater variation between shore level than between sites. Feeding experiments were conducted at 15°C with mussels collected from mid and low tide levels using Isochrysis galbana as the food. Clearance rate depended upon body size, shore level, and season. During summer clearance rates of mid and low tide mussels were similar. However in winter, increased filtration rates were recorded in mussels from the mid tide level compared with those from the low tide. In addition, for mussels from both shore levels, winter rates were higher than those recorded in the summer. Nitrogen excretion by mussels also showed seasonal and shore level differences. High values for ammonia excretion of mussels collected from the mid tide during winter suggests they utilise metabolic reserves to maintain their basal metabolism. Although our results suggest that increased filtration rates for mid tide mussels might compensate for reduced feeding time, in the winter, larger mussels from the mid tide level would be unlikely to obtain sufficient energy for maintenance or growth. Large mussels were infrequent in the mid tide population, where the mean length was 62.5 mm compared with 75.1 mm from the low tide. It is concluded that nutrient limitation, as a result of reduced feeding time can act as a significant stress factor limiting the growth potential of mussels settled at the mid tide level.